Case report: Duodenal obstruction caused by gastroduodenal artery pseudoaneurysm with hematoma: an unusual case and literature review - Zhou, Yan-Yuan; Wang, Shao-Chung; Seak, Chen-June; Huang, Shu-Wei; Cheng, Hao-Tsai (Frontiers in Medicine, 2023)
Visceral artery pseudoaneurysm is a rare disease which most commonly occur in male aged 50s, with gastroduodenal artery (GDA) pseudoaneurysm accounting for only 1.5% of them. The treatment options generally include open surgery and endovascular treatment. In the 40 cases of GDA pseudoaneurysm from 2001-2022, endovascular therapy is the mainstay of treatment (30 cases), and most of them (77%) are treated by coil embolization. Our case report describes a 76-year-old female patient of GDA pseudoaneurysm, which was treated by endovascular embolization using liquid embolic agent N-butyl-2-cyanoacrylate (NBCA) alone. This treatment strategy, to our best knowledge, is firstly used in GDA pseudoaneurysm. We demonstrate a successful outcome with this unique treatment. The successful experience of our case may provide a new treatment strategy for this rare disease.